2007
DOI: 10.1063/1.2773988
|View full text |Cite
|
Sign up to set email alerts
|

Widely tunable parametric amplifier based on a superconducting quantum interference device array resonator

Abstract: We create a Josephson parametric amplifier from a transmission line resonator whose inner conductor is made from a series SQUID array. By changing the magnetic flux through the SQUID loops, we are able to adjust the circuit's resonance frequency and, consenquently, the center of the amplified band, between 4 and 7.8 GHz. We observe that the amplifier has gains as large as 28 dB and infer that it adds less than twice the input vacuum noise.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
410
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(418 citation statements)
references
References 14 publications
5
410
3
Order By: Relevance
“…[22]. More sophisticated on-chip input/output circuitry, such as quantum limited amplifiers [23][24][25], circulators [26,27], and switching elements [28,29], will also be required for practical quantum information processing. This integration will likely be accompanied by through-wafer metalized vias to prevent cross-talk.…”
Section: Discussionmentioning
confidence: 99%
“…[22]. More sophisticated on-chip input/output circuitry, such as quantum limited amplifiers [23][24][25], circulators [26,27], and switching elements [28,29], will also be required for practical quantum information processing. This integration will likely be accompanied by through-wafer metalized vias to prevent cross-talk.…”
Section: Discussionmentioning
confidence: 99%
“…We note that, in practice, the smaller nonlinearity (dashed gray line) is obtained using junction arrays. Indeed, the Kerr nonlinearity with a junction array is inversely proportional to the square of the number of junctions in the array [4,9].…”
Section: A Deviation From Standard Dpa Resultsmentioning
confidence: 99%
“…Second, our results illustrate clearly the value of designing JPAs with small Kerr nonlinearities. This can be obtained by using SQUID arrays to dilute the nonlinearity [4,9] or adding additional linear inductance [36]. Finally, our work emphasizes the phase-sensitivity of the JPA in the high gain regime, and the importance of fully characterizing the phase and frequency dependence of the gain matrix in order to operate at the optimal phases and frequencies where the effects of nonidealities are minimal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties are utilized for various applications such as the development of the Fluxonion for quantum information precessing 5 , development of voltage standards in metrology 6 and for widely tunable parametric amplifiers 7 . Furthermore it is suggested that very long one-dimensional Josephson junction chains formed in a transmission line geometry can be employed for creating an analog of the event horizon and Hawking radiation 8,9 .…”
Section: Introductionmentioning
confidence: 99%